Effect of Organisational Development and Career Paths on Organisational Commitment and Civil Servant Performance at Hasanuddin University - Nur Ina Sarivina Nusu; Ria Mardiana Yusuf; Jumidah Maming (Magister Management, Hasanuddin University, 2020)
Human resource management is a strategic and decisive part. The organization and employees are one unit that has a relationship and must be balanced. To be able to support the achievement of organizational goals requires effort and hard work of all aspects of organizational resources to achieve organizational goals and objectives. The purpose of this study was to determine the effect of organizational development and career paths on organizational commitment and employee performance, organizational development, and career paths have an effect on employee performance through organizational commitment as an intervening variable. This research is a quantitative descriptive study. The sample used is civil servants (PNS), data collection techniques through questionnaires, while the techniques used are path analysis and Sobel test. The results showed that the organization and career path had a positive and significant effect on organizational commitment and employee performance. Organizational commitment has an effect on performance, then organizational development and career path have a positive and significant indirect effect on employee performance through organizational commitment in the Rector of Hasanuddin University.